Implementing Blended Learning within the TPMK Framework to Enhance Mathematics Teachers' Competence - Winarso, Widodo; Udin, Tamsik (Edelweiss Applied Science and Technology, 2024)
The post Covid-19 pandemic opens opportunities for teachers to conduct innovative studis in the context of mathematics education. The blended learning model has become the primary choice implemented by teachers during mathematics learning activities in schools. However, discourse related to this matter is still limited. This research investigates the impact of implementing the blended learning model on the Technological Pedagogical and Mathematics Knowledge (TPMK) of mathematics teachers in Madrasah Aliyah (MA) in Indonesia. post-Covid-19 pandemic. The research focuses on aspects of blended learning implementation, the level of TPMK of teachers, and the extent of its impact on the professional development of mathematics teachers. The research method used is correlational design, with data collection conducted through questionnaires given to MA teachers. The results show that implementing blended learning has a significant positive impact on improving the TPMK of mathematics teachers. Research recommendations include expanding training programs for teachers in technology integration, improving digital infrastructure in madrasas, providing incentives for learning innovations, and enhancing cooperation among madrasas. The implications of this research are crucial in providing significant contributions to the development of mathematics education in the madrasah environment. This research can be a foundation for developing more effective educational strategies and policies, particularly in facing and adapting to post-pandemic learning changes.